Malnutrition According to Mini Nutritional Assessment Is Associated With Severe Functional Impairment in Geriatric Patients Before and up to 6 Months After Hip Fracture - Goisser, Sabine; Schrader, Eva; Singler, Katrin; Bertsch, Thomas; Gefeller, Olaf; Biber, Roland; Bail, Hermann Josef; Sieber, Cornel; Volkert, Dorothee (Journal of the American Medical Directors Association, 2015)
Hip fractures (HFs) in old age frequently cause severe functional impairment and deteriorating autonomy in everyday life. Many older patients with HFs are malnourished or at risk of malnutrition. In this study, we examined the relationship between nutritional status of geriatric patients before HF and their functional and clinical course up to 6 months after hospital discharge.Observational study with follow-up after 6 months.Four wards of the department of trauma and orthopedic surgery of a large urban maximum care hospital (Klinikum Nürnberg, Nuremberg, Germany).Geriatric patients aged >=75 years with surgically repaired proximal femoral fracture.Prefracture nutritional status was determined by Mini Nutritional Assessment (MNA). Comorbidities and complications during hospital stay were obtained from medical documentation. Functional status before HF, postoperatively, at hospital discharge, and 6 months later was assessed by Barthel Index for activities of daily living (ADL) and patients' mobility level and related to MNA categories. Associations were evaluated using ?(2), Fisher exact, Kruskal-Wallis, Mann-Whitney-U, Jonckheere-Terpstra, and Cochrane-Armitage tests as appropriate, as well as analysis of covariance with repeated measures.Of 97 included patients, 17% were malnourished and 38% at risk of malnutrition before HF. Participants with (risk of) malnutrition were equally mobile but more dependent in ADL prior to HF than well-nourished patients (P < .001). Independent of nutritional status, after 6 months 68% of participants had not regained their prefracture level of independence in ADL. According to analysis of covariance, the ADL development over time until follow-up 6 months after hospital discharge did not depend on nutritional status. However, at follow-up malnourished patients more often suffered from remaining losses in ADL >=25% of initial Barthel Index points (P = .033) and less often had regained their prefracture mobility level (P = .020) than well-nourished patients. Clinical course did not differ significantly between the groups with different nutritional status.In this study with geriatric HF patients from all functional and cognitive levels, worse prefracture nutritional status was associated with worse functional status and more frequent remaining functional loss, whereas the trajectory of ADL recovery and clinical course did not differ significantly. Further studies with sufficient statistical power are needed to substantiate these inconclusive results. In order to clarify the association of nutritional status with functional and clinical course in geriatric patients after HF, they should preferably focus on the role of nutritional management during the hospital stay.
EVALuna2:5524